Reactivity of CS2 – Syntheses and Structures of Transition‐Metal Species with Dithioformate and Methanedithiolate Ligands. Issue 30 (15th September 2016) - Rao, Chokkapu Eswara; Barik, Subrat Kumar; Yuvaraj, K.; Bakthavachalam, K.; Roisnel, Thierry; Dorcet, Vincent; Halet, Jean‐François; Ghosh, Sundargopal
Abstract : The syntheses and structural characterization of the CS2 –metal complexes [(η 5 ‐C5 Me5 M)(η 2 ‐S2 CH2 )(η 3 ‐S2 CH)] (1 : M = Mo;2 : M = W), which feature partially and fully reduced CS2, are reported. In addition, the cis and trans isomers of the dimetallic (sulfido)molybdenum complexes [(η 5 ‐C5 Me5 Mo)2 (µ‐S2 CH2 S)2 ] (3 ‐ cis and4 ‐ trans ) are described. The [Mo2 S4 ] cores of3 ‐ cis and4 ‐ trans represent paddlewheel‐like arrays. All the new compounds were characterized in solution by mass spectrometry, IR spectroscopy, and 1 H and 13 C NMR spectroscopy. Their structural architectures were established by X‐ray crystallographic analysis. Quantum‐chemical calculations by DFT methods on the model compounds1′ –4′ ‐ trans showed good agreement with the experimentally observed structural parameters. The large HOMO–LUMO (HOMO = highest occupied molecular orbital, LUMO = lowest unoccupied molecular orbital) gaps are consistent with the high thermodynamic stabilities of these complexes. Further, the presence of short metal–metal cross‐cluster bonds in the X‐ray structures of3 ‐ cis and4 ‐ trans is supported by natural bond order (NBO) calculations. Abstract : We report the syntheses and structures of the CS2 ‐inserted group 6 transition‐metal complexes [(η 5 ‐C5 Me5 M)(η 2 ‐S2 CH2 )(η 3 ‐S2 CH)] (M = Mo, W) and the cis and trans isomers of the (sulfido)molybdenum complex [(η 5 ‐C5 Me5 Mo)2 (µ‐S2 CH2 S)2 ] (Cp* = η 5 ‐C5 Me5 )